Resisting Dehumanization: Female Experience of Stalin’s Gulag (KULT_online, 2021)
Survival as Victory: Ukrainian Women in the Gulag investigates the life of Ukrainian female political prisoners in Stalin’s Gulag (1939–1956). Oksana Kis discusses the development of Gulag studies and focuses on the individual human experience rather than on the penitentiary system by engaging with 150 female testimonies. Seven chapters of the book are devoted to different aspects and strategies of imprisonment survival, such as feeling of belonging, creativity, faith, love, and motherhood.